On-surface formation of polymers and molecular networks - Browning, Abigail S. (2019)
Self-assembly of ordered molecular structures on surfaces is of great interest in the formation of devices with novel properties. By utilising molecules that form ordered structures, structures can form spontaneously without the need for lithographic processes. The de-halogenation and polymerisation of 1,3,5-tris-(4-iodophenyl)benzene on the hBN surface was investigated with AFM, XPS and SIMS. The molecules were deposited both from solution and in vacuum in minor variations of the previously reported sine-wave structure. Above 100°C, polymerisation was observed with AFM and confirmed with SIMS, which revealed that, after polymerisation, additional iodine was still present suggesting that dehalogenation had not fully taken place prior to polymerisation occurring as suggested by the XPS results.